x-3y=-7

The slope-intercept form is y=mx+b, where m is the slope and b is the y-intercept.

y=mx+b

Subtract x from both sides of the equation.

-3y=-7-x

Divide each term by -3 and simplify.

Divide each term in -3y=-7-x by -3.

-3y-3=-7-3+-x-3

Cancel the common factor of -3.

Cancel the common factor.

-3y-3=-7-3+-x-3

Divide y by 1.

y=-7-3+-x-3

y=-7-3+-x-3

Simplify -7-3+-x-3.

Simplify each term.

Dividing two negative values results in a positive value.

y=73+-x-3

Dividing two negative values results in a positive value.

y=73+x3

y=73+x3

Reorder 73 and x3.

y=x3+73

y=x3+73

y=x3+73

Rewrite in slope-intercept form.

y=13x+73

y=13x+73

Rewrite in Slope-Intercept Form x-3y=-7